2016
DOI: 10.1016/j.ejphar.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A novel substituted aminoquinoline selectively targets voltage-sensitive sodium channel isoforms and NMDA receptor subtypes and alleviates chronic inflammatory and neuropathic pain

Abstract: Recent understanding of the systems that mediate complex disease states, has generated a search for molecules that simultaneously modulate more than one component of a pathologic pathway. Chronic pain syndromes are etiologically connected to functional changes (sensitization) in both peripheral sensory neurons and in the central nervous system (CNS). These functional changes involve modifications of a significant number of components of signal generating, signal transducing and signal propagating pathways. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 89 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…The effect of Kindolor to ameliorate pain in five animal models is described in our publication [ 56 ], and was provided as preliminary data on efficacy in our grant application. In addition we showed in our preliminary data a synergistic effect of Kindolor in combination with morphine or aspirin to reduce inflammatory pain (caused by Complete Freund’s Adjuvant) or diabetic neuropathic pain (caused by streptozotocin treatment), respectively.…”
Section: Approach and Results To Datementioning
confidence: 99%
See 3 more Smart Citations
“…The effect of Kindolor to ameliorate pain in five animal models is described in our publication [ 56 ], and was provided as preliminary data on efficacy in our grant application. In addition we showed in our preliminary data a synergistic effect of Kindolor in combination with morphine or aspirin to reduce inflammatory pain (caused by Complete Freund’s Adjuvant) or diabetic neuropathic pain (caused by streptozotocin treatment), respectively.…”
Section: Approach and Results To Datementioning
confidence: 99%
“…The illustrated actions of Kindolor are extrapolated from its measured actions on receptors and ion channels in model systems and demonstrations in the literature on the participation of the receptors/channels in generation and conduction of pain formation in sensory systems. It remains to be directly demonstrated that the antihyperalgesic actions of Kindolor are specifically mediated by the illustrated events [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N-methyl-D-aspartate (NMDA) receptors are relevant to chronic neuropathic pain, injury-induced pain behaviour and persistent pain of spinal lamina II neurons [10][11][12][13]. The NMDA receptor 2B subunit (N R 2B) shows a relatively restricted distribution in pathways of nociceptive transmission [14].…”
Section: ------------------------------------------------------------mentioning
confidence: 99%